Politik Hukum Agraria Terhadap Hak Ulayat Masyarakat Hukum Adat Di Indonesia - Yulia, Aris; Putri, Fatma Ayu Jati (Riviera Publishing, 2025)
The politics of agrarian law in Indonesia plays a crucial role in shaping the fate of indigenous peoples’ communal land rights (hak ulayat). Although the recognition of such rights is enshrined in the Constitution and several statutory regulations, their implementation remains limited. Regulatory disharmony, the absence of formal recognition of customary territories in many regions, and the stagnation of the Indigenous Peoples Bill (RUU Masyarakat Adat) reflect the state's weak commitment to protecting indigenous rights. Using a normative legal approach and analysis of relevant court decisions and policies, this article concludes that meaningful protection of hak ulayat requires agrarian policy reform rooted in social justice and legal pluralism.